AEETC—adaptive energy-efficient timing control in wireless networks with network coding - Li, Hongxing; Chan, Edward; Chen, Guihai (Telecommunication systems, 2010)
Energy is a scarce resource in wireless networks. Network coding has been proposed recently as a means to reduce the number of transmissions and energy consumption. In this paper, we introduce timing control into network coding to further enhance its performance. It is found that when bandwidth is sufficient, the extra delay introduced by waiting for additional data to perform network coding will increase the number of codings without affecting system throughput. Both delay and throughput suffers when bandwidth is insufficient. An adaptive energy-efficient timing control algorithm called AEETC is proposed which can automatically adjust local node’s transmission behavior on the basis of the network traffic conditions. Simulation results demonstrate that AEETC increases network coding by 7% to 60% for light network load and is able to provide good performance in terms of delay, throughput and the number of successful codings.